2017
DOI: 10.3389/fams.2017.00016
|View full text |Cite
|
Sign up to set email alerts
|

A Space-Time Study of Hemorrhagic Fever with Renal Syndrome (HFRS) and Its Climatic Associations in Heilongjiang Province, China

Abstract: Background: Hemorrhagic fever with renal syndrome (HFRS) is highly endemic in China, especially in Heilongjiang province (90% of all reported HFRS cases worldwide occur in China). The dynamic identification of high HFRS incidence spatiotemporal regions and the quantitative assessment of HFRS associations with climate change in Heilongjiang province can provide valuable guidance for HFRS monitoring, preventing and control. Yet, so far there exist very few and of limited scope quantitative studies of the spatiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 66 publications
2
12
0
Order By: Relevance
“…Future work could also focus on employing the dynamic transmission rate to forecast any trends in the numbers of COVID-19 cases, or to model patterns in future epidemics. Further, spatiotemporal disease characteristics (including the composite space-time disease dependencies and spread patterns using modern geostatistics methods, and their inter-association or tele-connection with climatic factors using time series, time-frequency methods ( Christakos and Olea, 2005 ; Christakos et al, 2005 ; Chirstakos, 2017 ; He et al, 2017 , He et al, 2018a , He et al, 2018b , He et al, 2019a , He et al, 2019b , He et al, 2019c ; Xiao et al, 2019 ; Jahangiri et al, 2020 ; Qi et al, 2020 ; Shi et al, 2020 ) could be explored by considering various levels of data, such as county-level or even individual-level disease data. More specifically, as was documented in the above literature, the geostatistics methods can help detect the trends, spread directions and core areas of the infectious disease.…”
Section: Discussionmentioning
confidence: 99%
“…Future work could also focus on employing the dynamic transmission rate to forecast any trends in the numbers of COVID-19 cases, or to model patterns in future epidemics. Further, spatiotemporal disease characteristics (including the composite space-time disease dependencies and spread patterns using modern geostatistics methods, and their inter-association or tele-connection with climatic factors using time series, time-frequency methods ( Christakos and Olea, 2005 ; Christakos et al, 2005 ; Chirstakos, 2017 ; He et al, 2017 , He et al, 2018a , He et al, 2018b , He et al, 2019a , He et al, 2019b , He et al, 2019c ; Xiao et al, 2019 ; Jahangiri et al, 2020 ; Qi et al, 2020 ; Shi et al, 2020 ) could be explored by considering various levels of data, such as county-level or even individual-level disease data. More specifically, as was documented in the above literature, the geostatistics methods can help detect the trends, spread directions and core areas of the infectious disease.…”
Section: Discussionmentioning
confidence: 99%
“…lower HFRS incidences), whereas Wusuli River, Songhua River and Mudan River locate in the eastern part of the province (i.e. higher HFRS incidences) [15]. Moreover, the eastern and southeastern parts of Heilongjiang Province exhibit mixed land types with forests, favoring rodents’ reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…During this period, the monthly rainfall, temperature and relative humidity ranged from 0.23 to 221.4 mm , -23.12 to 23.12 ° C and 38.77 to 83.74%, respectively. The Heilongjiang Province has 38.98, 26.29 and 16.92% croplands, mixed forests and cropland/natural vegetation mosaic, respectively [15]. In addition, the GDP of Heilongjiang Province increased from 551.4 to 1445.5 billion yuan .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that small-scale studies will yield more precise and a better quantification of the local characteristics of HFRS transmission, the present study chose four high-risk HFRSaffected counties from Heilongjiang and Shaanxi provinces, where the largest number of HFRS cases are documented in China. [9][10][11][12] It was found that HFRS variation exhibits multiannual cycles (especially around 1 year cycle) in various locations, for example, macroscopically, HFRS cases in China shows bimodal seasonal peaks, that is, May-June and November 8,11,13 ; microscopically, two main cycles (1 and 3-4 years) were detected by wavelet analysis in Changsha 4 ; similarly, HFRS cases in Xi'an also have a period of 0.8-1.2 years. 10 Moreover, it is reported that HFRS transmission is closely associated with the environmental factors, such as climatic variability and land-cover characteristics because the activity and population of virus hosts, which play an important role in HFRS transmission, are sensitive to these local environmental factors.…”
Section: Introductionmentioning
confidence: 99%